Innovative Methods for Intensifying the Processing of Zinc Clinker: Synergy of Microwave Treatment and Ultrasonic Leaching - Bagdaulet Kenzhaliyev; Tatiana Surkova; Ainur Berkinbayeva; Zhazira Baltabekova; Kenzhegali Smailov; Yerkezhan Abikak; Shynar Saulebekkyzy; Nazerke Tolegenova; Tursynkul Omirbek; Zamzagul Dosymbaeva (Metals)
This study presents an innovative approach to processing refractory zinc-bearing clinker through the synergistic application of microwave thermal treatment and ultrasonic-assisted leaching. Microwave irradiation induces phase transformations in the clinker, improving its reactivity and facilitating subsequent zinc dissolution, while ultrasonic cavitation enhances mass transfer by disrupting passivation layers. Key process parameters, including acid concentration, temperature, pulp density, and leaching time, were systematically investigated using response surface methodology (RSM) and central composite design (CCD). The results demonstrate that the optimized process conditions led to a significant increase in zinc recovery from refractory materials.